2019
DOI: 10.7150/jca.28495
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Gender and Body Mass Index in Asian Patients with Colorectal Cancer

Abstract: Objective: Colorectal cancer is a disease closely associated with anthropometric values. This study aimed to evaluate the clinical relevance of gender and body mass index (BMI) with colorectal cancer using a Korean nationwide cohort.Methods: Data of colorectal cancer cohorts between 2012 and 2013 were acquired from the Health Insurance Review and Assessment Service. All patients underwent surgery due to colorectal cancers. Stage IV patients were excluded due to possible clinical heterogeneity. BMI was classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…However, one study showed that underweight BMI showed no significant difference in OS compared to normal BMI in patients with stage III CRC (HR, 1.29; 95% CI, 0.77 to 2.19) [ 5 ], although the exact reason of this discordance was unclear. Some speculate that being underweight reflects a more advanced disease status and this may be translated into worse outcomes [ 8 , 23 ]. In our study, the rate of stage III also tended to be higher in patients with underweight BMI, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study showed that underweight BMI showed no significant difference in OS compared to normal BMI in patients with stage III CRC (HR, 1.29; 95% CI, 0.77 to 2.19) [ 5 ], although the exact reason of this discordance was unclear. Some speculate that being underweight reflects a more advanced disease status and this may be translated into worse outcomes [ 8 , 23 ]. In our study, the rate of stage III also tended to be higher in patients with underweight BMI, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed on the Korean population reported around 12% lower risk of distal cancer in the female than male patients. 52 The combinational study involving systematic review and meta-analysis from different geographic regions around the world revealed that men were at greater risk for advanced colorectal neoplasia. 53 The etiology for the difference remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses showed a significantly higher risk of colorectal polyps in male NAFLD cohort, whereas no risk was observed in the female cohort. A study performed on the Korean population reported around 12% lower risk of distal cancer in the female than male patients 52 . The combinational study involving systematic review and meta‐analysis from different geographic regions around the world revealed that men were at greater risk for advanced colorectal neoplasia 53 .…”
Section: Discussionmentioning
confidence: 99%
“…We inferred the results may be related to obesity and lipid metabolism. Obesity demonstrates a major public health issue because of its derived risk factors which are strongly associated with many diseases including CRC [25]. Studies have shown that decreased HDL is an important determinant of lipid peroxidation and it is of lower level in obese people than in others [26].…”
Section: Discussionmentioning
confidence: 99%